Integrated Use of Nitrogen Fertilizer and Fish Manure: Effects on the Growth and Chemical Composition of Spinach. Issue 13 (20th July 2019) - Ekinci, Melek; Atamanalp, Muhammet; Turan, Metin; Alak, Gonca; Kul, Raziye; Kitir, Nurgul; Yildirim, Ertan
ABSTRACT: Combinations of inorganic nitrogen and biological fertilizers are currently advised for integrated nutrient management. To prevent agricultural fish waste from polluting water sources, recycling of the organic waste of fish manure is advised. This study was conducted to determine effect of combinations of ammonium nitrate and fish manure on yield and spinach content under greenhouse conditions. Treatments consisted of fish manure (FM), ammonium nitrate (N) and the combination of fish manure and commercial fertilizer, with four doses of nitrogen (0, 100, 150 and 200 kg N ha −1 ). Applications significantly affected leaf and root fresh and dry weights, nutrient element, antioxidant enzymes and the flavonoid content of spinach. Plant growth, chemical composition and yield were superior in treatments with 150–200 kg ha −1 nitrogen doses with the combination of FM and N. FM application with N treatment provided maximum spinach yield and plant growth by reducing the use of commercial N fertilizer.